Learning and the digital workplace: What? So what? Now what?. Issue 6 (13th November 2017) - Noonan, Melissa; Richter, Gina; Durham, Larry; Pierce, Eric
Abstract : Purpose: The paper aims to describe the macro-level realities driving change for learning organizations and professionals including: volatility, uncertainty, complexity and ambiguity (VUCA) environment; information explosion; flattening organization; mobile and virtual workforce; and generational mix. It also describes implications for these realities and the critical shift from learning development to enablement via practices like learning curation, learning personalization, social learning and new and diverse learning modalities. Design/methodology/approach: The paper opted for a review of marketplace, business and industry trends, as well as reviews of specific primary research and current publications, to support its viewpoint. Findings: The VUCA of global; social; governmental; and economical systems is catalyzing the need for systemic change in the learning and development (L&D) industry. This will change the learning content that organizations will need to offer and the processes by which L&D leaders will need to identify and curate it. Originality/value: This paper fulfills the need to explain the necessity of changes required in skill sets and best practices for the modern learning organization.